Autonomy, Qualification and Professionalism of the PRC Bar - Luo, Qizhi (Columbia Journal of Asian Law, 1998)
In May 1996 the Lawyers’ Law of the People’s Republic of China (PRC) was promulgated to replace the PRC Provisional Regulations on Lawyers (hereafter referred to as the Regulations on Lawyers) in existence since 1980. The Lawyers’ Law represents a compromise resulting from the endeavors of the PRC authorities and the Chinese Bar to develop a moreprofessional and accountable legal community. This paper analyzes the evolution of the PRC legal community since the early 1980s. The changes in the PRC legal community have been phenomenal during the past decade. After the establishment of the Communist regime in 1949, lawyers in China had been degraded, frustrated, and trivialized for nearly three decades due to political campaigns. The legal community revived in the 1980s to provide legal services under the Regulations on Lawyers. Being charged with upholding the socialist legal system throughout their activities, for many years lawyers were de facto state authority figures.